The International Conference on Peace, Security, Democracy and Development in the Great Lakes Region, and conflict resolution in the Democratic Republic of Congo : a framework for multilateral preventive diplomacy - Solomon, Hussein (University of Pretoria, 2013)
Dissertation (MA (Political Science))--University of Pretoria, 2008.